An evaluation of BHW skills performance based on IMCI danger signs and cough training in three barangays in San Juan, Batangas - de Nieva, Marishielle E.; Katalbas, Eve Rizza G.; Posadas, John Joseph B.; Rey, Katrina Loren R.; Delfin, Maria Krisstella D.; Quintin, Maria Khrizalyn Faye J.; Umilin, Irene Tobey A.; Erni, Felice Lawrence Gale S.; Leynes, Chrystal J.
Introduction: The use of the IMCI strategy in the management of Danger Signs and Cough in children ages 0-5 years is being currently implemented in the municipality of San Juan, Batangas using the Inter-Disciplinary Approach (IDA) of the University of the Philippines — Manila. Comprehensive training programs on the IMCI module for Barangay Health Workers (BHW) have been started as part of the five-year plan of the Community Health Development Program. In line with this, the study aimed to evaluate the level of the competency of the BHWs in three barangays in San Juan, Batangas in skills performance of the IMCI Danger Signs and Cough.